Performance of Broiler - Chickens Fed on Maggot Meal in Place of Fishmeal - T.A.M., Awoniyi; Aletor, V.A.; Aina, J.M. (International Journal of Poultry Science, 2003)
Ninety 3-week old broiler-chickens were fed five isonitrogenous and isocaloric diets in which maggot-meal (MGM) which was first subjected to proximate analysis replaced 25, 50, 75 and 100% fishmeal (FM). The proximate analysis showed that MGM had 55.1% crude protein, 20.7% fat and 0.2% NFE. The data analysis, showed that weight gain (WG) Feed consumption (FC) and Feed efficiency (FE) for the chickens between 3-6 weeks of age were not significantly influenced by the dietary treatment whereas the WG, FC, FE, the nitrogen retention (NR) and protein efficiency ratio (PER) for the 3-9 week old were significantly (P>0.05) influenced by dietary treatment: The diet with 25% of FM protein replaced with MGM was the most efficient in terms of average weekly WG and PER. The live, dressed and eviscerated weights as well as the relative length, breadth and weights of the pectoral and gastrocnemius muscles of the chickens at 9 weeks were not significantly influenced by the diets. It was concluded that MGM is an inexpensive replacement for FM in broiler-chick feeding.